Influence of Nutrition Claims on Appetite Sensations according to Sex, Weight Status, and Restrained Eating - Geneviève Painchaud Guérard; Simone Lemieux; Éric Doucet; Sonia Pomerleau; Véronique Provencher (Hindawi Limited, 2016)
Nutrition claims may help people to adopt healthier eating habits, but little is known about the potential cognitive effects of such claims on appetite sensations. The main purpose of this study was to evaluate the impact of nutrition claims and individual factors on perceived appetite sensations. According to a three ("healthy" versus "diet" (i.e., satiating) versus "hedonic") by two (restrained or not restrained) by two (normal-weight or overweight/obese) by two (men versus women) factorial design, 164 males and 188 females aged 18-65 were invited to taste an oatmeal-raisin snack in a blinded and ad libitum context. Visual analog scales (150 mm) were used to evaluate appetite sensations before and over 1 h after consumption period. BMI and Restraint Scale were used to categorize participants according to their weight and restraint status. No main condition effect was observed for any of the four appetite sensations. However, subgroups analysis revealed significant differences among specific subgroups. A main effect of sex was also observed for all appetite sensations with men reporting higher levels of desire to eat, hunger and prospective food consumption, and lower levels of fullness than women. These findings highlight the importance of considering individual characteristics in interaction when studying appetite sensations.